Antiretroviral interventions to reduce mother-to-child transmission of human immunodeficiency virus: challenges for health systems, communities and society - Rachel Baggaley; Eric van Praag (Bulletin of the World Health Organization, 2000)
This paper examines the ethical, economic and social issues that should be considered when antiretroviral interventions are being planned to reduce mother-to-child transmission of the human immunodeficiency virus. Interventions aiming to reduce mother-to-child transmission should be concerned with the rights of both the child and the mother. Women should not be seen as vectors of transmission but as people entitled to adequate health care and social services in their own right. For women accepting mother-to-child transmission interventions it is important to consider their medical and emotional needs and to ensure that they are not stigmatized or subjected to abuse or abandonment following voluntary counselling and testing. Seropositive women who do not wish to continue with pregnancy should have access to facilities for safe termination if this is legal in the country concerned. Problems arise in relation to the basic requirements for introducing such interventions via the health services in developing countries. A framework is given for making decisions about implementation of interventions in health care systems with limited resources where there is a relatively high prevalence of human immunodeficiency virus infection among pregnant women.